2010
DOI: 10.1093/rpd/ncq015
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric CT examinations in 19 developing countries: frequency and radiation dose

Abstract: The aims of this study were to investigate the frequency of computed tomography (CT) examinations for paediatric patients below 15 y of age in 128 CT facilities in 28 developing countries of Africa, Asia and Eastern Europe and to assess the magnitude of CT doses. Radiation dose data were available from 101 CT facilities in 19 countries. The dose assessment was performed in terms of weighted CT dose index (CTDI(w)), volume CT index and dose length product (DLP) for chest, chest (high resolution), lumbar spine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 17 publications
2
40
0
2
Order By: Relevance
“…Si les efforts de l'AIEA portent des fruits avec la création d'une agence de radioprotection, la rareté des ressources contraint à la mise en oeuvre approximative des conventions internationales qui s'imposent en l'absence de cadre national (Muhogora et al, 2008(Muhogora et al, , 2010.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Si les efforts de l'AIEA portent des fruits avec la création d'une agence de radioprotection, la rareté des ressources contraint à la mise en oeuvre approximative des conventions internationales qui s'imposent en l'absence de cadre national (Muhogora et al, 2008(Muhogora et al, , 2010.…”
Section: Discussionunclassified
“…À l'opposé, dans les pays d'Afrique subsaharienne, les cadres législatifs et règlementaires sont soit inexistants soit mis en oeuvre de manière approximative et les pratiques de radioprotection des patients sont peu documentées alors que le parc scanographique s'accroît de manière constante depuis une décennie (Muhogora et al, 2008(Muhogora et al, , 2010Ongolo-Zogo et al, 2011). Dans le cadre d'un projet d'amélioration des pratiques de radioprotection, ce travail avait pour objectif d'évaluer, en termes dosimétriques, la pratique scanographique pédiatrique à Yaoundé au Cameroun.…”
Section: Introductionunclassified
“…A study conducted in developing countries estimated an increase in pediatric CT scan examination in Africa when compared to Asia and Eastern Europe. 1 CT scan examinations have a higher effective dose 2 and yet children have increased sensitivity to radiation 3,4 . This group of patients have more life years remaining to develop cancer and as well have proportionally more growing and developing tissue and organ systems than adults which calls for a special radiation protection concern.…”
Section: Introductionmentioning
confidence: 99%
“…8 Contrary to this, studies showed a lack of awareness and malpractice leading to higher radiation doses to children. 9 Hollingsworth et al noted 20-25% of the CT scan operators did not know the scan parameters that they use for scanning children. 10 Similar findings were noted in several African countries as noted by Muhogora et al 9 All the mentioned discrepancies call for the establishment of standard operating parameters during CT scan procedure which is a major concern in pediatric patient's radiation protection.…”
Section: Introductionmentioning
confidence: 99%
“…Different procedures about the indication, dosage of Head CT and repeated CT used common in pediatric TBI have been performed in different centers (3)(4).…”
Section: Introductionmentioning
confidence: 99%